The Influence of Financial Literacy, Financial Accounting Learning and Lifestyle on Student Financial Behavior - Purwoningsih, Siti Khotimah; Solikah, Mar'atus; Linawati, Linawati (Universitas Nusantara PGRI Kediri, 2024)
Research objectives: The purpose of this study is to examine the influence of financial literacy, financial accounting learning, and lifestyle on financial behavior in students, especially students of the Faculty of Economics and Business at the Accounting Study Program of Universitas Nusantara PGRI Kediri Design/Method/Approach: The method in this study is quantitative-based. The sample was taken using a nonprobability sampling technique of purposive sampling type and a sample of 124 respondents from accounting students of Universitas Nusantara PGRI Kediri batch 2020-2021. Data analysis and processing using the software SPSS Research Findings: Findings from the study show that there is a partial and simultaneous influence of financial literacy, financial accounting learning, and lifestyle on financial behavior Theoretical Contribution: This research is expected to develop knowledge and reference sources as well as scientific development regarding financial behavior in students. Practitioner Implications: This research is expected to be used as evaluation material for financial assessment as well as consideration and input to provide socialization about finance, especially among students. Research Limitations: The limitations of this research are the data source used was only a questionnaire and the sample limit only included accounting study program students